Photothermal self-healing coating containing modified graphene oxide and preparation method and application thereof
Patent Information
- Application Number
- CN202611182452.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-30
AI Technical Summary
若先将TA与GO混合再引入铁盐,TA的邻苯二酚基团会优先吸附于GO表面并趋于饱和,导致后续与Fe3+配位不充分,生成游离或低效络合物,难以构建致密、均匀的功能层
1、本发明对氧化石墨烯进行改性,通过特定的加料顺序先将单宁酸与三氯化铁预配位形成完整的Fe3+-TA金属-多酚配位网络,再将其致密沉积于经聚乙烯吡咯烷酮预先分散的氧化石墨烯片层表面,避免了现有技术利用氧化石墨烯时因单宁酸在氧化石墨烯表面吸附饱和导致配位不充分、形成游离或低效络合物的缺陷,在氧化石墨烯表面成功构建了具有高效宽波段光热转换能力和丰富界面键合锚点的多功能层。
Smart Images

Figure CN123004232A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of self-healing anti-corrosion coating technology, specifically relating to photothermal self-healing coatings containing modified graphene oxide, their preparation methods, and applications. Background Technology
[0002] Metal corrosion is a major cause of steel structure failure in coastal environments. Traditional anti-corrosion coatings rely on physical shielding; once microcracks or damage occur, corrosive media penetrate and cause localized corrosion. Self-healing anti-corrosion coatings have attracted much attention because they can actively or passively repair damage. They are divided into two categories: exogenous (microcapsule-released repair agents) and endogenous (reversible chemical bond or physical stimulus response). Among them, photothermal-triggered self-healing has become a research hotspot due to its remote operability and precise positioning.
[0003] Photothermal conversion materials are crucial for achieving this function. Graphene oxide (GO) is widely used due to its unique conjugated system, good compatibility, and excellent photothermal response; its physical barrier effect can delay the penetration of corrosive media. However, the stability and dispersibility of GO remain key bottlenecks that need improvement. Existing modification strategies, such as polyaniline deposition, can enhance barrier properties and dispersibility, but they mostly focus on single properties, with insufficient research on the synergistic relationship between adhesion, self-healing efficiency, and anti-corrosion performance. Furthermore, these strategies suffer from problems such as complex preparation, high cost, and demanding repair conditions.
[0004] Previous studies have combined tannic acid (TA), iron salts, and graphene-based materials, but none have recognized that the structural integrity of the metal-polyphenol coordination network (MPN) is highly dependent on the order of addition. If TA and GO are mixed first and then iron salts are introduced, the catechol groups of TA will preferentially adsorb onto the GO surface and tend to become saturated, leading to subsequent adhesion with Fe... 3+ Insufficient coordination leads to the formation of free or inefficient complexes, making it difficult to construct a dense and uniform functional layer. Furthermore, existing technologies only focus on the individual effects of each component, failing to achieve an effective balance between high adhesion, high self-healing rate, and long-term corrosion protection. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides a photothermal self-healing coating containing modified graphene oxide. By pre-constructing a metal-polyphenol network and combining it with polyvinylpyrrolidone pre-dispersion and silane coupling anchoring, efficient photothermal conversion, interface enhancement, and intrinsic self-healing are simultaneously achieved on the GO surface, taking into account both comprehensive performance and process economy.
[0006] This invention is achieved through the following technical solution: This invention provides a method for preparing a photothermal self-healing coating containing modified graphene oxide, comprising the following steps: S1. Modified graphene oxide was prepared by modifying graphene oxide with tannic acid, ferric chloride hexahydrate and polyvinylpyrrolidone. S2. Disperse the prepared modified graphene oxide and polyvinylpyrrolidone in a solvent, add a silane coupling agent, and obtain a uniform dispersion. S3. Add the dispersion to the epoxy resin substrate and mix evenly. Then add the curing agent, pigments and fillers, leveling agent and defoamer. After stirring evenly, a photothermal self-healing coating containing modified graphene oxide can be obtained.
[0007] Furthermore, in step S2, the weight ratio of modified graphene oxide to polyvinylpyrrolidone is 1:2.
[0008] Furthermore, in step S2, the weight ratio of modified graphene oxide to silane coupling agent is 1:1.3.
[0009] Furthermore, in step S3, the weight ratio of modified graphene oxide to epoxy resin is 1:66.7.
[0010] Furthermore, in step S3, the weight ratio of the curing agent to the epoxy resin substrate is 1:2.9, and the weight ratio of the pigments and fillers to the epoxy resin substrate is 1:10.
[0011] Furthermore, the method for preparing the modified graphene oxide includes the following steps: S11. Graphene oxide and polyvinylpyrrolidone were ultrasonically dispersed in anhydrous ethanol to obtain a dispersion. S12. After dissolving tannic acid, add ferric chloride hexahydrate and stir until homogeneous to obtain a mixed solution; S13. After adding the mixture to the dispersion, allow the reaction to proceed fully. Centrifuge, wash, and dry the reaction solution to obtain the modified graphene oxide.
[0012] Furthermore, in step S11, the weight ratio of graphene oxide to polyvinylpyrrolidone is 1:2.
[0013] Furthermore, in step S12, the weight ratio of ferric chloride hexahydrate to tannic acid is 1:3.
[0014] The present invention also provides a photothermal self-healing coating containing modified graphene oxide prepared according to the above preparation method.
[0015] The present invention also provides a photothermal self-healing coating containing modified graphene oxide for use in preparing anti-corrosion coatings to prevent metal corrosion.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention modifies graphene oxide by pre-coordinating tannic acid with ferric chloride to form complete Fe through a specific feeding sequence.3+ A TA metal-polyphenol coordination network was then densely deposited on the surface of graphene oxide sheets pre-dispersed with polyvinylpyrrolidone. This avoids the defects of existing technologies that use graphene oxide, such as insufficient coordination and the formation of free or inefficient complexes due to the adsorption saturation of tannic acid on the graphene oxide surface. A multifunctional layer with efficient broadband photothermal conversion capability and abundant interfacial bonding anchors was successfully constructed on the graphene oxide surface.
[0017] 2. The modified graphene oxide (TPFG) prepared in this invention possesses three functions: photothermal conversion, interface enhancement, and intrinsic self-healing. Coatings prepared using the modified graphene oxide prepared in this invention can be processed via Fe... 3+ The synergistic effect of the TA coordination network with polyvinylpyrrolidone and silane coupling agents simultaneously achieves the monodispersity of nanofillers, chemical bonding and anchoring with epoxy groups, and dynamic and reversible hydrogen bonding and coordination bond repair of the network.
[0018] 3. The anti-corrosion coating system formed using the coating provided by this invention achieves a high initial adhesion of 18.02 MPa, a 98% self-healing rate of 30 μm scratches under near-infrared light irradiation, a 75% adhesion retention rate after damp heat aging, and a low-frequency impedance modulus maintained at 107.2 Ωcm after 30 days of salt spray testing. 2 The above-mentioned long-term anti-corrosion performance breaks through the bottleneck of existing technologies that make it difficult to achieve both high adhesion, high self-healing efficiency and long-term anti-corrosion performance, and has the potential for large-scale application and broad market prospects. Attached Figure Description
[0019] Figure 1 This is a flowchart of the preparation process and a schematic diagram of the performance testing of the modified graphene oxide of this invention. Figure 2 This is a flowchart illustrating the preparation process of the photothermal self-healing coating containing modified graphene oxide of the present invention. Figure 3 The Fourier transform infrared (FT-IR) spectra of graphene oxide and modified graphene oxide in the embodiments of the present invention are shown. Figure 4 The X-ray diffraction (XRD) patterns of graphene oxide and modified graphene oxide in the embodiments of the present invention are shown. Figure 5 Thermogravimetric analysis (TGA) curves of graphene oxide and modified graphene oxide in the embodiments of the present invention; Figure 6 The images shown are SEM surface morphology images of the products obtained in the examples; where 6a is the SEM surface morphology image of graphene oxide. Figure 6 b is the SEM surface morphology of the modified graphene oxide. Figure 6 c is the EDS energy spectrum of graphene oxide. Figure 6d is the EDS energy spectrum of the modified graphene oxide; Figure 7 The image shows a test diagram of the self-healing performance of the coating formed by curing the coating obtained from the comparative product of this invention. Figure 8 This is a test diagram of the photothermal conversion performance of the coating formed by curing the coating obtained from the comparative product of this invention; Figure 9 The images show the electrochemical performance test results of the coatings formed by curing the coatings obtained from the comparative products of this invention in the initial state, after scratching, and after self-healing. Figure 10 Surface morphology images of coatings after salt spray acceleration experiments at different experimental times in embodiments of the present invention; Figure 11 The adhesion test results of the coating formed by curing the coating obtained from the comparative product of this invention are shown in the figure. Figure 12 The graph shows the adhesion test results of the coatings formed by curing the coatings obtained from the comparative products of this invention before and after aging. Detailed Implementation
[0020] The present invention will be further described below with reference to preferred embodiments and the accompanying drawings. The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges. These numerical ranges should be considered as specifically disclosed herein. Unless otherwise specified, all materials and reagents used in the following examples are commercially available; and all experimental methods used in the following examples are conventional methods unless otherwise specified.
[0021] Unless otherwise specified, the raw materials, reagents or devices used in the following examples are available from conventional commercial sources or can be obtained by existing known methods.
[0022] Example 1 This embodiment provides a method for preparing modified graphene oxide, referring to... Figure 1 Flowchart of the preparation process of modified graphene oxide. Figure 1 The modified graphene oxide composite coating mentioned above is made of modified graphene oxide and includes the following steps: S11. Graphene oxide and polyvinylpyrrolidone (PVP) K30 were ultrasonically dispersed in anhydrous ethanol at a molar ratio of 1:2. The ultrasonic dispersion was carried out in a water bath at a temperature of 55°C for 30 minutes to obtain a dispersion. S12. Dissolve tannic acid in deionized water, add ferric chloride hexahydrate, wherein the molar ratio of tannic acid to ferric chloride hexahydrate is 1:3, and stir magnetically in a water bath at 60°C for 20 minutes to obtain a mixed solution. S13. After adding the mixture to the dispersion, allow it to react fully. Stir magnetically at 60°C for 30 minutes. After the reaction is complete, cool the mixture to room temperature and centrifuge at 9000 rpm for 10 minutes. Take the precipitate, wash it three times with deionized water, and dry it thoroughly at 60°C. After drying, grind it to obtain modified graphene oxide.
[0023] The structure and composition of the modified graphene oxide (TPFG) prepared above are analyzed as follows: 1. Fourier Transform Infrared Spectroscopy (FIR) Test Test results are as follows Figure 3 As shown, the black curve corresponding to the modified graphene oxide (TPFG) exhibits significant shape changes and peak shifts compared to the red curve, confirming the successful introduction of the PVP and Fe-TA complex onto the GO (graphene oxide) surface. The black curve is located at 3000-3500 cm⁻¹. 1 The absorption peak at that point becomes very flat, and the intensity decreases significantly. The hydroxyl groups do not completely disappear; rather, it's because the phenolic hydroxyl groups in TA react with Fe. 3+ A coordination reaction occurred, forming a metal-polyphenol network (Fe-TA), which consumed free phenolic hydroxyl groups. Simultaneously, hydrogen bonding between PVP and GO or TA also restricted the -OH vibration. Furthermore, the hydrophobic carbon framework coating may have reduced the adsorbed water content. GO originally had a concentration at 1730 cm⁻¹. 1 The carboxyl vibration peak at 1640 cm⁻¹ is almost completely disappeared or obscured in the black curve. 1 A relatively sharp, strong absorption peak appeared nearby, which is key evidence of successful modification. This new peak is mainly attributed to the amide I band (C=O stretching vibration) in PVP. Typically, the amide peak of PVP is around 1660 cm⁻¹. 1 The peak position may redshift (move to lower wavenumbers) due to hydrogen bonding with tannic acid or GO. Simultaneously, the skeletal vibration of the benzene ring in tannic acid (C=C) also contributes to this region, and the superposition of these two factors forms the main peak.
[0024] 2. X-ray diffraction (XRD) test Tests such as Figure 4As shown, the modified graphene oxide (TPFG) curve underwent significant changes. The characteristic peak near 10° weakened, and the sharp 001 peak, originally belonging to graphene oxide, transformed into a very weak and broad bulge after modification. This indicates the disruption of interlayer regularity; PVP molecules and Fe-TA complexes successfully inserted into the GO interlayer or coated the surface, breaking the original regular stacked structure. Simultaneously, a tendency for exfoliation emerged, and the GO sheets no longer stacked neatly but existed in a more dispersed state. A very broad peak appeared near 22.5°, which is usually attributed to the amorphous structure. On the one hand, due to the polymer coating, PVP itself is an amorphous polymer, and this broad peak reflects the coating of PVP on the GO surface and its own amorphous diffraction; on the other hand, the metal-polyphenol network (MPN) formed by Fe-TA is also an amorphous coating, covering the GO sheets and further masking the crystalline characteristics of the carbon material itself. By comparing the XRD data before and after modification, it was confirmed that PVP and Fe-TA were not simply physically mixed with GO, but were tightly bound to the GO sheets through interactions.
[0025] 3. Thermogravimetric analysis (TGA) test Test results are as follows Figure 5 As shown, the red curve TFG represents modified graphene oxide. Modified graphene oxide and graphene oxide (GO) exhibit distinctly different thermal behaviors in their pyrolysis characteristics. The stability at low temperatures is improved; near 200℃, modified graphene oxide does not show the drastic, precipitous weight loss seen in GO. This indicates that the highly active oxygen-containing functional groups on the GO surface are stabilized through PVP and Fe-TA modification, and some oxygen-containing groups react with the modifiers during the modification process. Modified graphene oxide shows a significant mass decrease in the 300℃~450℃ range, primarily due to the decomposition of PVP (typically between 350℃ and 450℃), and the degradation of the Fe-TA complex. Tannins and their metal-polyphenol network (MPN) formed with iron also undergo pyrolysis in this temperature range. This confirms that PVP and Fe-TA have been successfully loaded onto GO sheets, and their mass proportions are significant. Analysis shows that the modified material exhibits significantly enhanced chemical stability below 200℃, successfully eliminating the thermal instability of pure GO in the mid-to-low temperature range. Although the introduction of organic components such as PVP results in substantial mass loss at high temperatures, this composite structure makes the material more reliable in processing and mid-temperature applications.
[0026] 4. Scanning Electron Microscopy (SEM) Testing Test results are as follows Figure 6 As shown, Figure 6Image a shows a SEM image of graphene oxide (GO), which exhibits a distinct smooth and wrinkled structure on the surface, with large agglomerations between the sheets. This is due to the high surface energy of the GO sheets and the abundance of oxygen-containing functional groups on the surface, which makes them prone to mutual compression and bending during macroscopic stacking. Figure 6 b represents the modified graphene oxide (GO). It is evident that the original wrinkles are significantly reduced, and the surface becomes relatively smooth and thick. The interlayer wrinkles of GO are opened and peeled off into sheets, large wrinkles disappear, and a microscopic roughness due to material deposition can be observed on the surface. The edges of the sheets are rounded or blurred, indicating that the edges are also covered by a coating layer, demonstrating that the modification significantly improves the aggregation phenomenon of GO. Figure 6 c and Figure 6 Compared to d, the oxygen content decreased from 38.34 to 30.27, while the nitrogen and iron contents increased. This indicates that iron has been successfully loaded onto the surface of the modified graphene oxide. The changes in these values are attributed to the introduction of TA and Fe-TA networks with high oxygen content and the coordination consumption of some oxygen-containing functional groups on the GO surface. This further confirms that a stable interfacial bond has been formed between TA molecules and hydroxyl / carboxyl groups on the GO surface through hydrogen bonds and interactions.
[0027] Example 2 This embodiment provides a photothermal self-healing coating containing modified graphene oxide, the preparation method of which is as follows. Figure 2 The specific steps are as follows: S1. 0.1 wt% of modified graphene oxide and polyvinylpyrrolidone (PVP) K30 were ultrasonically dispersed in a mixed solvent of anhydrous ethanol and deionized water for 30 min, and silane coupling agent KH-560 was added to obtain a uniform dispersion A. S2. Add dispersion A to 50g of epoxy resin substrate, stir for 10min to mix evenly, and obtain mixed dispersion B; S3. Add 17.5g of curing agent to the mixed dispersion B and stir mechanically for 15min. Add 7.5g of pigment and filler (titanium dioxide) and continue stirring until uniform. Then add 0.3g of leveling agent and 0.3g of defoamer in sequence and stir mechanically for 15min to obtain 0.1% of photothermal self-healing coating (EP-TPFG) containing modified graphene oxide.
[0028] Example 3 This embodiment provides a method for preparing a photothermal self-healing coating containing modified graphene oxide. In step S1, the amount of modified graphene oxide is 0.5 wt%, and the remaining steps are the same as in Example 2, to obtain 0.5% photothermal conversion self-healing coating (EP-TPFG) containing modified graphene oxide.
[0029] Example 4 This embodiment provides a method for preparing a photothermal self-healing coating containing modified graphene oxide. In step S1, the amount of modified graphene oxide is 1.0 wt%, and the remaining steps are the same as in Example 2, to obtain 1.0% photothermal conversion self-healing coating (EP-TPFG) containing modified graphene oxide.
[0030] Example 5 This embodiment provides a method for preparing a photothermal self-healing coating containing modified graphene oxide. In step S1, the amount of modified graphene oxide is 1.5 wt%, and the remaining steps are the same as in Example 2, to obtain 1.5% photothermal conversion self-healing coating (EP-TPFG) containing modified graphene oxide.
[0031] Example 6 This embodiment provides a method for preparing a photothermal self-healing coating containing modified graphene oxide. In step S1, the amount of modified graphene oxide is 2.0 wt%, and the remaining steps are the same as in Example 2, to obtain a 2.0% photothermal conversion self-healing coating (EP-TPFG) containing modified graphene oxide.
[0032] Comparative Example 1 In this comparative example, graphene oxide was used to replace the modified graphene oxide in step S1, with an amount of 1.5 wt%. The remaining steps were the same as in Example 2, and the coating EP-GO1.5 was obtained.
[0033] Comparative Example 2 In this comparative example, no modified graphene oxide or graphene oxide was added, and the remaining steps were the same as in Example 2 to obtain pure EP coating.
[0034] Application Examples The coatings obtained in Examples 1-6 and Comparative Examples 1 and 2 were applied to Q235 steel sheets to form coatings, and the coatings were subjected to relevant performance tests.
[0035] 1. Adhesion test: The adhesion between the coating and carbon steel was tested using the pull-off test method of the GBT31586.1-2015 Protective Coating System for Corrosion Protection Coatings on Steel Structures - Evaluation and Acceptance Criteria Part 1.
[0036] 2. Self-healing performance test: The coatings formed by the paints prepared in the examples and comparative examples were scratched with a scalpel and then examined under a metallographic microscope using a power density of 1.0 W / cm². 2 The coating was irradiated with near-infrared light at a distance of 20cm, and the self-healing effect of the scratches was recorded.
[0037] 3. Photothermal conversion test: A near-infrared light emitter with a power density of 1.0 W / cm² was used. 2The coating was subjected to a comparative test by irradiating a portion of it with near-infrared light at a distance of 20cm, and the coating temperature was recorded in real time using a high-precision thermocouple thermometer.
[0038] 4. Corrosion resistance test: Using EP-TPFG 1.5% as the sample, the electrochemical performance of the coating was characterized by carbon steel samples. The electrochemical behavior of carbon steel samples coated with the coating, as well as carbon steel samples with scratches and repairs, in 3.5 wt% NaCl solution was recorded using a CHI660E electrochemical workstation. Coatings with different coatings were scratched and then placed in salt spray, and the macroscopic appearance of the surface was recorded at different times.
[0039] Performance test results 1) Adhesion test results are as follows Figure 7 , Figure 8 As shown. By Figure 7 It can be seen that the dry adhesion of the coating first increases and then decreases with the increase of modified graphene oxide (TPFG) content. EP-TPFG 1.5% reaches a peak of 18.02 MPa, which is about 64.5% higher than 1.5% GO (EP-GO 1.5% coating prepared in Comparative Example 1) and about 158% higher than the blank (pure EP coating prepared in Comparative Example 2). EP-TPFG 2.0% shows a significant decrease, with an adhesion of only 16.37 MPa; the results of the aging experiments are as follows... Figure 8 As shown, the adhesion of EP-TPFG 1.5% and EP-TPFG 1.0% before and after aging is higher than that of pure EP and EP-GO 1.5%. One key factor is the multiple chemical bonding; TA and KH-560 silane coupling agents were used in the preparation, acting as links in the system. Tannic acid contains a large number of catechol groups, exhibiting strong chemical affinity and chelating ability for carbon steel, forming stable chemical bonds at the interface. Another factor is the increased surface roughness of the TPFG sheets. During curing, the resin carries the nanosheets deep into the micropores of the substrate surface, forming a stronger mechanical interlocking effect. Furthermore, the addition of PVPK30 prevents secondary aggregation of GO in ethanol. Good dispersibility ensures that the nanoparticles are uniformly distributed on the contact surface between the coating and the substrate, maximizing the effective contact area.
[0040] 2) Self-healing performance test results are as follows Figure 9 As shown, Figure 9 EP-TFG 1.0% and EP-TFG 0.5%The experimental groups with TPFG contents of 1.0 wt% and 1.5 wt% in the coatings provided by this invention showed the best scratch healing effects, reaching 95% and 98%, respectively. The control groups with EP-GO (1.5%) and EP showed poor self-healing performance. This is mainly attributed to TA-Fe... 3+ As a highly efficient photothermal conversion center, the complex utilizes its wide-band light absorption characteristics to rapidly convert absorbed photon energy into lattice vibrational thermal energy through a non-radiative relaxation process. Simultaneously, the steric hindrance effect of the long-chain PVP ensures the monodisperse state of TPFG within the epoxy resin matrix, constructing a uniform and continuous three-dimensional thermal conductivity network. This structural advantage allows the coating to overcome the low thermal conductivity of the polymer matrix, rapidly transferring heat to the scratch root and deep interfaces, providing a thermodynamic basis for subsequent chain segment movement. The introduction of TPFG nanoparticles disrupts the compactness of the epoxy resin crosslinking network, increasing the free volume between polymer chain segments. Under photoexcitation, the local temperature of the coating rapidly rises above Tg, and the matrix undergoes a physical phase transition from a glassy state to a viscous flow state.
[0041] 3) Photothermal conversion test results are as follows Figure 10 As shown, the photothermal conversion of the coating mainly occurs within the first 50 seconds, during which the coating temperature rises rapidly. The EP-TPFG1.5% coating temperature can reach a maximum of 80℃, exhibiting excellent photothermal conversion performance and providing a foundation for the rapid self-healing of the coating. These changes are mainly attributed to PVP K30 as a surfactant, which ensures the dispersibility of modified graphene oxide in ethanol and resin. Good dispersion means more uniform heating and higher conversion efficiency. KH-560 acts as a bridging agent for the silane coupling agent, making the modified graphene oxide bond more tightly to the epoxy resin matrix. This not only helps with dispersion but also reduces the interfacial thermal resistance between nanoparticles and resin, allowing heat to be conducted more quickly to the entire coating.
[0042] 4) Corrosion resistance test: Results are as follows Figure 11 As shown, the impedance value of EP-TPFG1.5% is 6.29 × 10⁻⁶. 8 Ω·cm 2 This indicates that the coating possesses excellent corrosion resistance. The impedance value of the coating after scratching is 7.33 × 10⁻⁶. 4 Ω·cm 2 This indicates that the coating has been scratched through, and its anti-corrosion effect has been greatly affected. The impedance modulus of the scratch after complete healing under near-infrared light irradiation is 4.37 × 10⁻⁶. 8 Ω·cm 2 The impedance value was four orders of magnitude higher than when the scratch occurred, and no new time constant appeared, indicating that the anti-corrosion performance of the coating on the surface had been well restored; the salt spray test results were as follows. Figure 12As shown, with the extension of salt spray immersion time, the blank sample showed the most severe rust diffusion, while the 1.5%wt TPFG sample showed the least rust and the best self-healing anti-corrosion effect.
[0043] Table 1 shows a comparison of the economic efficiency of the coatings and related products obtained by this invention. From an economic perspective, although this invention introduces modified components such as TA, FeCl3, and PVP, their optimal addition amounts in the epoxy system are only 1.0 wt% and 1.5 wt%, respectively, and the matrix still uses a conventional epoxy resin system. Therefore, the initial material cost is low. The self-healing ability of the coating was tested, and the test results are shown in Table 2. Compared with EP-TPFG, EP-GO1.5% and EP, it also showed good performance in terms of adhesion, self-healing performance and corrosion resistance. It can effectively reduce the frequency of later maintenance and extend the service life. Therefore, its total life cycle cost is lower than that of conventional anti-corrosion coating systems.
[0044] Table 1. Economic Comparison of Coatings and Related Products Obtained by the Invention
[0045] Table 2. Test data on the self-healing performance of coatings prepared from the coatings obtained in the embodiments and comparative examples of the present invention.
[0046] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a photothermal self-healing coating containing modified graphene oxide, characterized in that, Includes the following steps: S1. Modified graphene oxide was prepared by modifying graphene oxide with tannic acid, ferric chloride hexahydrate and polyvinylpyrrolidone. S2. Disperse the prepared modified graphene oxide and polyvinylpyrrolidone in a solvent, add a silane coupling agent, and obtain a uniform dispersion; S3. Add the dispersion to the epoxy resin substrate and mix evenly. Then add the curing agent, pigments and fillers, leveling agent and defoamer. After stirring evenly, a photothermal self-healing coating containing modified graphene oxide can be obtained.
2. The preparation method of the photothermal self-healing coating containing modified graphene oxide as described in claim 1, characterized in that, In step S2, the weight ratio of modified graphene oxide to polyvinylpyrrolidone is 1:
2.
3. The preparation method of the photothermal self-healing coating containing modified graphene oxide as described in claim 1, characterized in that, In step S2, the weight ratio of modified graphene oxide to silane coupling agent is 1:1.
3.
4. The preparation method of the photothermal self-healing coating containing modified graphene oxide as described in claim 1, characterized in that, In step S3, the weight ratio of modified graphene oxide to epoxy resin is 1:66.
7.
5. The preparation method of the photothermal self-healing coating containing modified graphene oxide as described in claim 1, characterized in that, In step S3, the weight ratio of curing agent to epoxy resin substrate is 1:2.9, and the weight ratio of pigments and fillers to epoxy resin substrate is 1:
10.
6. The preparation method of the photothermal self-healing coating containing modified graphene oxide as described in claim 1, characterized in that, The method for preparing the modified graphene oxide includes the following steps: S11. Graphene oxide and polyvinylpyrrolidone were ultrasonically dispersed in anhydrous ethanol to obtain a dispersion. S12. After dissolving tannic acid, add ferric chloride hexahydrate and stir until homogeneous to obtain a mixed solution; S13. After adding the mixture to the dispersion, allow the reaction to proceed fully. Centrifuge, wash, and dry the reaction solution to obtain the modified graphene oxide.
7. The photothermal self-healing coating containing modified graphene oxide as described in claim 6, characterized in that, In step S11, the weight ratio of graphene oxide to polyvinylpyrrolidone is 1:
2.
8. The photothermal self-healing epoxy resin composite coating as described in claim 6, characterized in that, In step S12, the weight ratio of ferric chloride hexahydrate to tannic acid is 1:
3.
9. A photothermal self-healing coating containing modified graphene oxide, prepared by the method according to any one of claims 1 to 8.
10. A photothermal self-healing coating containing modified graphene oxide as described in claim 9 is used to prepare an anti-corrosion coating to prevent metal corrosion.
